Elevated Semaphorin 5A correlated with Th1 polarization in patients with chronic immune thrombocytopenia. Issue 5 (November 2015) - Lyu, Mingen; Li, Yang; Hao, Yating; Sun, Tiantian; Liu, Wenjie; Lyu, Cuicui; Fu, Rongfeng; Li, Huiyuan; Xue, Feng; Liu, Xiaofan; Zhang, Lei; Yang, Renchi
Abstract: Background: Primary immune thrombocytopenia (ITP) is an immune-mediated disorder in which cellular immunity deficiency and disturbed cytokine profiles have been found. Semaphorin 5A (Sema5A) has been showed to be implicated in cellular immune response. We aimed to evaluate the role of Sema5A in patients with chronic ITP. Methods: Plasma levels of Sema5A, T helper (Th) cytokines (interferon [IFN] -γ, interleukin [IL]-4, IL-17A) were determined by enzyme-linked immunosorbent assay (ELISA) in ITP patients and healthy controls. Using real-time quantitative polymerase chain reaction (RT-PCR), mRNA levels of Sema5A and its receptor plexin-B3, plexin-A1 in peripheral blood mononuclear cells(PBMCs)were studied in all subjects. Specific anti-platelet autoantibodies were measured by the Pak Auto method. The dynamic change of plasma Sema5A and mRNA levels of its receptors was measured in 9 patients after effective therapy. Results: Plasma Sema5A levels were significantly increased in active patients with chronic ITP compared to patients in remission and healthy controls. Elevated levels of Sema5A were found positively correlated with higher levels of plasma IFN-γ, IFN-γ/IL-4 ratio and negatively correlated with lower levels of plasma IL-4, platelet counts in ITP patients. The mRNA plexin-B3 was decreased in active ITP patients and inversely correlated with plasma Sema5A levels. Additionally, plasma levels of Sema5A and IFN-γ were reduced with up-regulation of plexin-B3 expression after effective treatment. Conclusions: Our data demonstrated elevated plasma Sema5A in chronic ITP patients might be involved in Th1 polarization by down-regulating receptor plexin-B3 expression and correlated with disease activity. Highlights: Higher level of Plasma Sema5A was observed in chronic ITP patients. Plasma Sema5A was positively correlated with the plasma IFN-γ, IFN-γ/IL-4 ratio. Plasma Sema5A was inversely correlated with receptor plexin-B3 expression. Decreased plasma Sema5A and elevated plexin-B3 mRNA were found after treatment.